2005
DOI: 10.3748/wjg.v11.i28.4375
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gastrointestinal and extra-gastrointestinal symptoms and delayed gastric emptying in functional dyspeptic patients

Abstract: Abstract Abstract Abstract AIM: Delayed gastric emptying and an enlarged fasting gastric antrum are common findings in functional dyspepsia but their relationship with gastrointestinal (GI), and the frequently associated extra-GI symptoms remains unclear. This study evaluated the relationship between GI and extra-GI symptoms, fasting antral volume and delayed gastric emptying in functional dyspepsia. METHODS:In 108 functional dyspeptic patients antral volume and gastric emptying were assessed with ultrasonogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Delayed gastric emptying has been described in approximately 20 to 40% of patients with FD (Talley et al, 2001;Sarnelli et al, 2003;Lorena et al, 2004;Pallotta et al, 2005), and postprandial gastric antral hypomotility has been shown in patients with FD (Kusunoki et al, 2000). Gastroprokinetic agents are probably useful for the treatment of FD, and symptoms do subside with an improvement in gastric motility dysfunction (Talley, 1995;Allescher et al, 2001;Mizuta et al, 2006).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed gastric emptying has been described in approximately 20 to 40% of patients with FD (Talley et al, 2001;Sarnelli et al, 2003;Lorena et al, 2004;Pallotta et al, 2005), and postprandial gastric antral hypomotility has been shown in patients with FD (Kusunoki et al, 2000). Gastroprokinetic agents are probably useful for the treatment of FD, and symptoms do subside with an improvement in gastric motility dysfunction (Talley, 1995;Allescher et al, 2001;Mizuta et al, 2006).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Although standard diagnostic tests in patients with FD fail to identify an underlying organic abnormality (Talley et al, 1999), delayed gastric emptying has been described in approximately 20 to 40% of patients (Talley et al, 2001;Sarnelli et al, 2003;Lorena et al, 2004;Pallotta et al, 2005). Patients with FD have also shown postprandial gastric antral hypomotility (Kusunoki et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These patients frequently complain of upper abdominal symptoms such as bloating, upper abdominal discomfort or pain, and vomiting. The symptoms overlap with lower abdominal symptoms and are resistant to dietary and pharmacological treatments because of the constipation issues; they are related to the presence of impaired gastrointestinal myoelectrical activity and reduced upper gastrointestinal motor activity (1,4,13,31,33,37). This phenomenon has led to the hypothesis that rectal distension (RD) with fecal stasis in the colorectal region directly causes reflexive inhibition of proximal gastrointestinal motility (5,7,9,22,32,50).…”
mentioning
confidence: 99%
“…On nuclear scans for a subset of patients with GERD, we documented conditions of delayed gastric emptying that may be contributors to the nonresponding symptoms [14]. Pallotta et al [20] documented the relationship of persistent gastrointestinal symptoms and delayed gastric emptying in dyspeptic patients. Cahan et al [21] showed that PPI therapy may be a causative factor in depressing digestive output.…”
Section: Discussionmentioning
confidence: 99%